Fetal alcohol spectrum disorder: an exploratory telehealth pilot group intervention for caregivers. - Burkhart, Kimberly; Lipman, Catherine; Agarwal, Neel; Tangen, Rachel; Bothe, Denise (Children's Health Care)
The Family Foundations: Behavioral, Emotional, Social, and Team-Based [B.E.S.T.] program is a novel trauma-informed intervention for caregivers of children with Fetal Alcohol Spectrum Disorders (FASD) to address emotional, behavioral, and cognitive problems. Twenty-five caregivers participated in this exploratory pilot study and completed pre- and post-intervention questionnaires. There was a significant decrease in child externalizing behavioral problems and total problems (p <.01). There was a significant decrease in caregiver stress (p <.01) and an increase in self-reported parenting confidence (p <.01). Mixed results were obtained for change in child social functioning. Further evaluation with a control group and larger sample size is needed to further assess the effectiveness of the program.